Investigating the failure behaviors of RC beams without stirrups under impact loading. (March 2020) - Fu, Yingqian; Yu, Xinlu; Dong, Xinlong; Zhou, Fenghua; Ning, Jianguo; Li, Ping; Zheng, Yuxuan
Highlights: The real-time evolution of crack patterns is visualized by high-speed camera and digital image correlation. Failure-mode transitions are characterized for RC beams without stirrups with increasing impact velocities. Shear plug initiates at the loading point before reaching the maximum value of impact force. Impact resistance is primarily dominated by the global resistance of structure and local failure of materials at flexural-and shear-failure mode, respectively. Absorbed energy decreases with increasing impact velocity at shear-failure mode. Abstract: This study visualizes the evolution of crack patterns for simply-supported RC beams under static and impact loadings using the techniques of DIC and high-speed camera. At relatively low impact velocity, we observe multiple flexural cracks developing in a progressive sequence from mid-span to supports. At relatively high impact velocity, we observe a shear plug initiated at loading point during early time before impact response reaching supports. The critical velocity for transition from flexural- to shear-failure mode varies from 6.9 to 8.4 m/s. Comparative analysis suggests the impact resistance is related to failure modes: The maximum impact force is controlled by global resistance of structure at flexural-failure mode, while it is controlled by local failure of materials at shear-failure mode. Finally, this study compares absorbed energy with impact velocity at flexural- and shear-failure modes. By increasing impact velocity, the results show that absorbed energy increases at flexural-failure mode, and decreases at shear-failure mode. The decreasing absorbed energy capacity is possibly caused by less plastic deformation of steel reinforcements in a more concentrated zone of shear plug at shear-failure mode.